The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/ccr3.4705
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of percutaneous balloon pulmonary valvuloplasty in congenital pulmonary valve stenosis

Abstract: Percutaneous balloon pulmonary valvuloplasty (PBPV) is the primary treatment for pulmonary valve stenosis (PVS). The study consisted of 228 children with PVS who underwent PBPV from January 2004 to October 2019 at a single center. The risk factors for ≥moderate pulmonary regurgitation (PR), residual stenosis, and restenosis were analyzed based on the baseline patient characteristics and measured value of corresponding inspection results. Among 228 patients, follow‐up results were obtained in 193 patients. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
6
0
5
Order By: Relevance
“…Jaing et al (22) reported that the success rate was 90%. The immediate success rate was 89.6% with Yin et al (23) . The possible cause of this difference may be due to the selection bias in our study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Jaing et al (22) reported that the success rate was 90%. The immediate success rate was 89.6% with Yin et al (23) . The possible cause of this difference may be due to the selection bias in our study.…”
Section: Discussionmentioning
confidence: 87%
“…This result is equivalent to that of Peterson et al (25) , who discovered the development of restenosis in 13 (14.1%) of patients who had undergone BPV; 6 individuals were re-dilated, and 7 individuals required surgery (their study involved 108 patients with a mean age of 3.6 years). According to Yin et al (23) , reported 16.6% of 193 individuals with follow-up data with residual stenosis or restenosis after initial BPV, with 9 needing reintervention.…”
Section: Discussionmentioning
confidence: 99%
“…La estenosis pulmonar es una cardiopatía congénita acianótica que representa, aproximadamente, 8 a 10% de los defectos cardiacos al nacimiento 1 , 2 . Su presentación puede ser asintomática, con un hallazgo incidental de un soplo, o de grado severo con cianosis, dolor torácico, disnea y falla cardiaca 3 - 5 .…”
Section: Introductionunclassified
“…3 Studies have described percutaneous balloon valvuloplasty to have immediate success with reintervention requirement in fewer cases along with reasonable growth of the RV and that of the pulmonary valve in infants with critical pulmonary valve stenosis. 4,5 However, the procedure often presents technical difficulties because of increased pressure in the RV making it difficult to reach the stenotic pulmonary valve. To overcome this issue certain methods have been devised and used around the world like using a catheter with bent hard end of a guide wire and using trans-jugular approach instead of the routinely used femoral vein.…”
Section: Introductionmentioning
confidence: 99%